Health Professionals' and Postpartum Women's Perspectives on Digital Health Interventions for Lifestyle Management in the Postpartum Period: A Systematic Review of Qualitative Studies - Lim, Siew; Tan, Andrea; Madden, Seonad; Hill, Briony (Frontiers in Endocrinology, 2019)
Objective: To explore postpartum women and health professionals’ perspectives of digital health interventions (DHIs) for lifestyle management in postpartum women. Design: A systematic review and thematic synthesis of peer-reviewed qualitative studies. Relevant databases were searched from 1990 to 2019. Study quality was appraised using the Critical Appraisal Skills Programme (CASP) Qualitative Checklist. Setting and participants: Studies describing postpartum women’s or health professionals’ views regarding DHIs for lifestyle management in postpartum women. Findings: Nine studies were included for thematic synthesis. Four common themes emerged: ‘personal facilitators and barriers to lifestyle modification’, ‘intervention-related strategies for lifestyle modification’, ‘user experience of the technology’, ‘suggestions for improvement’. The review indicated that DHIs are highly acceptable among postpartum women. Postpartum women valued behaviour change strategies that were delivered through DHIs including goal-setting and self-monitoring, however personal barriers such as lack of motivation or childcare priorities were cited. Key conclusions and implications for practice: Digital health interventions should be considered for lifestyle management in postpartum women. The development of DHIs should focus on delivering behaviour change strategies and addressing practical barriers faced by postpartum women.